An electrochemical method for preparing cis-hexahydrophthalic anhydride from phthalic anhydride in one step

By using a supported Pt3Rh electrocatalyst in a proton exchange membrane reactor for electrochemical galvanostatic electrolysis, the problems of complex preparation process, many side reactions, and low purity of hexahydrophthalic anhydride in the existing technology are solved, and one-step efficient and high-efficiency production of phthalic anhydride is achieved. Green and gentle preparation of cis-hexahydrophthalic anhydride improves product purity and current efficiency.

CN115772674BActive Publication Date: 2025-01-17DALIAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211513188.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-03
Filing Date
2022-11-29
Publication Date
2025-01-17
Estimated Expiration
2042-11-29

AI Technical Summary

Technical Problem

In the prior art, the preparation process of hexahydrophenyl anhydride has multiple steps, incomplete hydrogenation, many side reactions, difficulty in separation, harsh conditions of traditional thermal catalytic methods, and cis-trans isomerization problems, affecting product purity.

Method used

Using electrochemical methods at room temperature and normal pressure, a supported Pt3Rh electrocatalyst was developed, and galvanostatic electrolysis was performed through a proton exchange membrane reactor to achieve one-step highly selective conversion of phthalic anhydride into cis-hexahydrophthalic anhydride.

Benefits of technology

The efficient, green, and gentle one-step preparation of cis-hexahydrophthalic anhydride from phthalic anhydride is achieved, which avoids the energy consumption and operating risks caused by high temperature and high pressure in traditional thermal catalysis, and improves product purity and current efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115772674B_ABST
    Figure CN115772674B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of fine chemicals, and discloses an electrochemical method for preparing cis-hexahydrophthalic anhydride from phthalic anhydride in one step. By developing a supported Pt3Rh electrocatalyst for efficient benzene ring hydrogenation, it is highly selectively converted into high-value-added chemical cis-hexahydrophthalic anhydride in one step, thereby realizing resource utilization of phthalic anhydride. The method uses clean and sustainable water as a hydrogen source, with mild reaction conditions and is green and environmentally friendly. With a proton exchange membrane reactor as a reaction device, continuous production can be achieved and catalyst coking and deactivation caused by traditional thermal catalysis can be effectively avoided. The conversion rate of phthalic anhydride, the selectivity of cis-hexahydrophthalic anhydride, and the current efficiency can all reach more than 90%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fine chemicals and relates to an electrochemical method for preparing cis-hexahydrophthalic anhydride by hydrogenating phthalic anhydride in one step. Background Art

[0002] Hexahydrophthalic anhydride (hexahydrophthalic anhydride) is an important raw material in the production of polyester high-end coatings. The amino alkyd acid, polyurethane paint, powder coating, etc. produced by using hexahydrophthalic anhydride instead of aromatic polyacids have obvious advantages, which can improve the gloss of the coating, reduce the viscosity, and significantly improve the weather resistance of the coating. Hexahydrophthalic anhydride can also be used in the production of plasticizers, pesticides, rust inhibitors, etc., especially as a curing agent for epoxy resins. Since epoxy resins can be made into coatings, composite materials, casting materials, adhesives, molding materials and injection molding materials, they are widely used in various fields of the national economy, making the demand for hexahydrophthalic anhydride increasing day by day.

[0003] In industry, tetrahydrophthalic anhydride obtained by addition of maleic anhydride and 1,3-butadiene is often used as raw material, and further catalytic hydrogenation is performed to obtain hexahydrophthalic anhydride. This method has many steps. During the hydrogenation process, the double bonds of tetrahydrophthalic anhydride are easily transferred, resulting in incomplete hydrogenation. Under the action of hydrogen atoms, the anhydride is also very likely to undergo side reactions such as condensation, hydrogenolysis, and cross-linking, generating impurities that are difficult to separate. The boiling points of tetrahydrophthalic anhydride and hexahydrophthalic anhydride are close, making it difficult to effectively separate them by traditional methods such as distillation. In addition, high-boiling point byproducts are easily coked at the reaction temperature, resulting in catalyst poisoning and deactivation.

[0004] Hexahydrophthalic anhydride can also be prepared by one-step hydrogenation of phthalic anhydride (o-phthalic anhydride), usually under high temperature and high pressure, using hydrogen as the hydrogen source, which is prone to explosion. Studies in recent years have found that the hexahydrophthalic anhydride obtained by this method has two isomers, cis and trans, which cannot be separated, affecting the purity of the product. In addition, due to differences in spatial structure, the thermodynamic stability of the cis isomer is usually worse than that of the trans isomer. Therefore, it is very important to find a green, mild, and convenient method for preparing high-purity cis hexahydrophthalic anhydride.

[0005] The following known technologies all have some shortcomings:

[0006] Chinese patent, publication number: CN109225227A, introduces an ordered mesoporous carbon catalyst for preparing hexahydrophthalic anhydride and its preparation method. The method uses non-precious metal Ni as the active component of the catalyst and tetrahydrophthalic anhydride as the reactant to prepare hexahydrophthalic anhydride with high selectivity. However, the catalyst synthesis process of this method is complicated, and the existing phthalic anhydride hydrogenation to produce hexahydrophthalic anhydride is not fully utilized.

[0007] The Chinese patent, publication number: CN 104785250A, introduces a method for producing hexahydrophthalic anhydride by highly selective hydrogenation using mesoporous carbon as a carrier, Ru as an active component, and phthalic anhydride as a raw material. However, the metal Ru loading is high, the reaction conditions are relatively harsh, and the maximum hydrogen pressure can reach 10MPa.

[0008] Chinese patent, publication number: CN 106674172A, discloses a method of preparing hexahydrophthalic anhydride by hydrogenating phthalic anhydride using eggshell-type PdRu as catalyst and phthalic anhydride as raw material through organic combination of solvent recovery and distillation. However, this method produces byproducts such as phthalide, o-methylbenzoic acid and o-methylcyclohexylcarboxylic acid, and the generated hexahydrophthalic anhydride contains a small amount of trans structure, which is difficult to further purify. Summary of the invention

[0009] The present invention provides an electrochemical method for preparing cis-hexahydrophthalic anhydride. With the purpose of rationally utilizing phthalic anhydride as a resource, and in view of the relatively harsh conditions of the traditional thermal catalytic method, the hydrogenation product has cis-trans isomerism and other problems, a supported Pt3Rh electrocatalyst for efficient benzene ring hydrogenation is developed by adopting an electrochemical method at room temperature and normal pressure, so as to realize the resource utilization of phthalic anhydride. Since the benzene ring is mainly adsorbed on the surface of the working electrode in a planar manner, and all atoms of phthalic anhydride are coplanar, the adsorbed hydrogen (H ad ) and the carbon atoms at positions 1 and 2 in the benzene ring of phthalic anhydride are combined on the same side, and finally converted into high value-added chemical cis-hexahydrophthalic anhydride with high selectivity in one step. The proton exchange membrane reactor (PEM) is used as the reaction device, which has high current efficiency and can be produced continuously, and can effectively avoid the catalyst coking and deactivation caused by traditional thermal catalysis. The reaction formula is as follows:

[0010]

[0011] The technical solution of the present invention:

[0012] An electrochemical method for preparing cis-hexahydrophthalic anhydride from phthalic anhydride in one step, the steps are as follows:

[0013] A proton exchange membrane reactor was used as the reaction device, and a carbon cloth-supported Pt3Rh alloy was used as the cathode material. Phthalic anhydride was dissolved in 1,4-dioxane to prepare a cathode electrolyte for constant current electrolysis, wherein the concentration of phthalic anhydride was 0.5M to 1.0M and the current density was -5 to -10 mA / cm 2 The reaction temperature is 50-80°C. A peristaltic pump is used to pump the electrolyte flowing out of the cathode chamber back into the cathode chamber to continue the hydrogenation reaction. The flow rate is 2-5 mL / h. After 2-6 hours, the product cis-hexahydrophthalic anhydride is collected at the cathode chamber outlet.

[0014] The loading amount of Pt3Rh alloy is 2wt.% to 5wt.% of the mass of the carbon cloth.

[0015] The PEM reactor is purified using anode and cathode raw materials before the electrolysis reaction is carried out.

[0016] The beneficial effects of the present invention are as follows: the catalyst synthesis process of the method is simple, and more importantly, the reaction conditions are mild, water is used as the hydrogen source, and it is green and environmentally friendly, avoiding the energy consumption and operation hazards caused by high temperature and high pressure in traditional thermal catalysis. At the same time, phthalic anhydride can be highly selectively converted into cis-hexahydrophthalic anhydride in one step, with high current efficiency and continuous synthesis, thus solving the problem of cis-trans isomerization of the product in thermal catalysis, which affects the purity of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is the SEM image of 3wt% Pt3Rh alloy catalyst supported on carbon cloth. DETAILED DESCRIPTION

[0018] The present invention will be described in detail below by way of examples. The examples described below are exemplary and are only used to explain the present invention, but the present invention is not limited to these examples.

[0019] Example 1

[0020] A 2wt.% to 5wt.% Pt3Rh alloy catalyst loaded on carbon cloth was prepared by the impregnation-hydrogen reduction method. The specific preparation method is as follows: Take a certain amount of aqueous solution of H2PtCl6·6H2O and RhCl3·3H2O of known concentration and add it to a vial, so that the atomic ratio of Pt and Rh is 3:1, and the proportion of metal to carbon cloth (2cm×2.5cm, about 0.0650g) is 2wt.% to 5wt.%, and ultrasonicate until the metal salt precursor is evenly mixed. The carbon cloth is immersed in the precursor solution, dried at room temperature, and reduced at 400°C in a tubular furnace for 2 hours under a hydrogen atmosphere, and then passivated under an argon atmosphere to obtain a 2wt.% to 5wt.% Pt3Rh catalyst loaded on the carbon cloth, of which a 3wt.% Pt3Rh catalyst loaded on the carbon cloth is shown. Figure 1 shown.

[0021] Example 2

[0022] A carbon cloth loaded with 3 wt.% Pt3Rh was used as the cathode, and a carbon cloth loaded with Pt was used as the anode. Phthalic anhydride and 1,4-dioxane were mixed evenly to prepare an electrolyte with a phthalic anhydride concentration of 0.5 M. The electrolysis current was -5 mA / cm 2 The reaction temperature was kept constant at 50°C, and the PEM was purified for 30 minutes with the feeds from the anode and cathode. During the reaction, the electrolyte flowing out of the cathode was recirculated and pumped into the cathode at a liquid flow rate of 2 mL / h. After 6 hours, the product was collected for gas chromatography analysis. The conversion rate of phthalic anhydride was 90%, the selectivity of cis-hexahydrophthalic anhydride was 93%, and the current efficiency was 90%.

[0023] Example 2

[0024] A carbon cloth loaded with 2 wt.% Pt3Rh was used as the cathode, and a carbon cloth loaded with IrO2 was used as the anode. Phthalic anhydride and 1,4-dioxane were mixed evenly to prepare an electrolyte with a phthalic anhydride concentration of 0.2 M. The electrolysis current was -2 mA / cm 2 The reaction temperature was kept constant at 50°C, and the PEM was purified for 30 minutes with the feeds from the anode and cathode. During the reaction, the electrolyte flowing out of the cathode was recirculated and pumped into the cathode at a liquid flow rate of 1 mL / h. After 8 hours, the product was collected for gas chromatography analysis. The conversion rate of phthalic anhydride was 81%, the selectivity of cis-hexahydrophthalic anhydride was 89%, and the current efficiency was 72%.

[0025] Example 3

[0026] A carbon cloth loaded with 3 wt.% Pt3Rh was used as the cathode, and a carbon cloth loaded with Pt was used as the anode. Phthalic anhydride and 1,4-dioxane were mixed evenly to prepare an electrolyte with a phthalic anhydride concentration of 0.8 M. The electrolysis current was -8 mA / cm 2 The reaction temperature was kept constant at 60°C, and the PEM was purified for 30 minutes with the feeds from the anode and cathode. During the reaction, the electrolyte flowing out of the cathode was recirculated and pumped into the cathode at a liquid flow rate of 3 mL / h. After 5 hours, the product was collected for gas chromatography analysis. The conversion rate of phthalic anhydride was 92%, the selectivity of cis-hexahydrophthalic anhydride was 94%, and the current efficiency was 91%.

[0027] Example 4

[0028] A carbon cloth loaded with 3 wt.% Pt3Rh was used as the cathode, and a carbon cloth loaded with Pt was used as the anode. Phthalic anhydride and 1,4-dioxane were mixed evenly to prepare an electrolyte with a phthalic anhydride concentration of 1.0 M. The electrolysis current was -8 mA / cm 2 The reaction temperature was kept constant at 70°C, and the PEM was purified for 30 minutes with the feeds from the anode and cathode. During the reaction, the electrolyte flowing out of the cathode was recirculated and pumped into the cathode at a liquid flow rate of 4 mL / h. After 3 hours, the product was collected for gas chromatography analysis. The conversion rate of phthalic anhydride was 93%, the selectivity of cis-hexahydrophthalic anhydride was 97%, and the current efficiency was 92%.

[0029] Example 5

[0030] A carbon cloth loaded with 3 wt.% Pt3Rh was used as the cathode, and a carbon cloth loaded with IrO2 was used as the anode. Phthalic anhydride and 1,4-dioxane were mixed evenly to prepare an electrolyte with a phthalic anhydride concentration of 1.0 M. The electrolysis current was -10 mA / cm 2The reaction temperature was kept constant at 80°C, and the PEM was purified for 30 minutes with the feeds from the anode and cathode. During the reaction, the electrolyte flowing out of the cathode was recirculated and pumped into the cathode at a liquid flow rate of 5 mL / h. After 4 hours, the product was collected for gas chromatography analysis. The conversion rate of phthalic anhydride was 93%, the selectivity of cis-hexahydrophthalic anhydride was 97%, and the current efficiency was 92%.

[0031] Example 6

[0032] A carbon cloth loaded with 5wt.% Pt3Rh was used as the cathode, and a carbon cloth loaded with IrO2 was used as the anode. Phthalic anhydride and 1,4-dioxane were mixed evenly to prepare an electrolyte with a phthalic anhydride concentration of 1.0M. The electrolysis current was -12mA / cm 2 The reaction temperature was kept constant at 80°C, and the PEM was purified for 30 minutes with the feeds from the anode and cathode. During the reaction, the electrolyte flowing out of the cathode was recirculated and pumped into the cathode at a liquid flow rate of 8 mL / h. After 4 hours, the product was collected for gas chromatography analysis. The conversion rate of phthalic anhydride was 82%, the selectivity of cis-hexahydrophthalic anhydride was 88%, and the current efficiency was 67%.

[0033] Comparative Example 1

[0034] A 3wt.% Pt3Ru alloy catalyst supported on carbon cloth was prepared according to the method in Example 1, except that a certain amount of aqueous solution of H2PtCl6·6H2O and RuCl3·3H2O of known concentration was taken. The 3wt.% Pt3Ru alloy catalyst supported on carbon cloth was used as the cathode material, and cis-hexahydrophthalic anhydride was prepared according to the process conditions in Example 2. Since the activation ability of the single metal Ru itself to the benzene ring is worse than that of Rh, and there is a strong overlap between the d orbital electron density of Pt and Rh atoms, which is greater than that of Pt and Ru atoms, under the same conditions, the conversion rate of Pt3Ru to phthalic anhydride decreases. In addition, Ru itself is more active than Rh in the hydrogen evolution reaction, which intensifies hydrogen production and slightly decreases the current efficiency. In this comparative example, the conversion rate of phthalic anhydride is 82%, the selectivity of cis-hexahydrophthalic anhydride is 86%, and the current efficiency is 83%.

[0035] Comparative Example 2

[0036] A 3wt.% PtRh3 alloy catalyst supported on carbon cloth was prepared according to the method in Example 1, except that: a certain amount of H2PtCl6·6H2O and RhCl3·3H2O aqueous solution of known concentration was taken to make the atomic ratio of Pt and Rh be 1:3. The 3wt.% PtRh3 alloy catalyst supported on carbon cloth was used as the cathode material, and cis-hexahydrophthalic anhydride was prepared according to the process conditions in Example 2. Since the activation ability of the single metal Rh itself to the benzene ring is worse than that of Pt, under the same conditions, although a higher current efficiency can be maintained, the conversion rate of PtRh3 to phthalic anhydride decreases. At the same time, the price of Rh is higher than that of Pt, which increases the catalyst cost and is not conducive to actual production. In this comparative example, the conversion rate of phthalic anhydride is 76%, the selectivity of cis-hexahydrophthalic anhydride is 85%, and the current efficiency is 88%.

[0037] Comparative Example 3

[0038] The 3wt.% Pt3Rh alloy catalyst loaded on carbon cloth was prepared according to the method in Example 1, and the cis-hexahydrophthalic anhydride was prepared according to the process conditions in Example 2, with the difference that the reaction was carried out at room temperature. Because the driving ability to protons at room temperature is lower than that under high temperature, and at the same time, the aromatic ring and anhydride structure contained in phthalic anhydride make the molecular structure relatively complex and the bond energy higher, the activation of the carbon-hydrogen bond in the benzene ring cannot be achieved when the temperature is low, and the solubility is also slightly poor. In this comparative example, the conversion rate of phthalic anhydride is 64%, the selectivity of cis-hexahydrophthalic anhydride is 79%, and the current efficiency is 83%.

[0039] Comparative Example 4

[0040] According to the method in Example 1, an 8wt.% Pt3Rh alloy catalyst loaded on carbon cloth was prepared, except that: the proportion of metal in carbon cloth was 8wt.%. The 8wt.% Pt3Rh alloy catalyst loaded on carbon cloth was used as the cathode material, and cis-hexahydrophthalic anhydride was prepared according to the process conditions in Example 2. Due to the high metal loading, the metal nanoparticles are unevenly dispersed and the particle size is larger after hydrogen reduction, which is 20-30nm, which is significantly larger than the 2wt.%-5wt.% Pt3Rh alloy catalyst with a particle size of 8-12nm. The uneven dispersion leads to partial agglomeration of the surface metal nanoparticles, which is not conducive to the exposure of active sites; at the same time, the particle size is larger, the specific surface area is smaller, and the surface active centers are less, resulting in a significant decrease in the conversion rate under the same reaction conditions. In this comparative example, the conversion rate of phthalic anhydride is 57%, the selectivity of cis-hexahydrophthalic anhydride is 79%, and the current efficiency is 65%.

Claims

1. An electrochemical method for preparing cis-hexahydrophthalic anhydride from phthalic anhydride in one step, characterized in that: A proton exchange membrane reactor was used as the reaction device, and a carbon cloth-supported Pt3Rh alloy was used as the cathode material. Phthalic anhydride was dissolved in 1,4-dioxane to prepare a cathode electrolyte for constant current electrolysis, wherein the concentration of phthalic anhydride was 0.5M to 1.0M and the current density was -5 to -10 mA / cm 2 The reaction temperature is 50-80°C. A peristaltic pump is used to pump the electrolyte flowing out of the cathode chamber back into the cathode chamber to continue the hydrogenation reaction. The flow rate is 2-5 mL / h. After 2-6 hours, the product cis-hexahydrophthalic anhydride is collected at the cathode chamber outlet.

Citation Information

Patent Citations

  • Hydrogenation catalyst, its preparation method and its application in preparation of hexahydrophthalic anhydride

    CN104785250A

  • Method for preparing hexahydrophthalic anhydride

    CN106674172A

  • Ordered mesoporous carbon catalyst for preparing hexahydrophthalic anhydride and preparation method thereof

    CN109225227A

  • Electrochemical method for preparing cis-hexahydrophthalic anhydride from phthalic anhydride in one step

    CN114293208A